Climate change aggravated wildfire behaviour in the Iberian Peninsula in recent years - Martín Senande-Rivera; Damián Insua-Costa; Gonzalo Miguez-Macho (npj Climate and Atmospheric Science)
Abstract Climate change is considered to affect wildfire spread both by increasing fuel dryness and by altering vegetation mass and structure. However, the direct effect of global warming on wildfires is hard to quantify due to the multiple non-climatic factors involved in their ignition and spread. By combining wildfire observations with the latest generation of climate models, here we show that more than half of the large wildfires (area>500 ha) occurring in the Iberian Peninsula between 2001 and 2021 present a significant increase in the rate of spread with respect to what it would have been in the pre-industrial period, attributable to global warming. The average acceleration of the rate of spread due to increased fuel dryness is between 2.0% and 8.3%, whereas the influence of enhanced vegetation growth since the pre-industrial period could potentially be even higher than the direct impact of temperature increase in fuel conditions.